Исследование инвариантных особенностей перспективных преобразований для задач компьютерного зрения - Путятин, Е. П.; Любченко, В. А.; Передрий, Е. О. (ХНУРЭ, 2008)
In the work analysis of the influence of the image perspective distortions on its weight centers is researched on the basis of moment theory. Dependence between values of the central moment and direction of the axis of perspective transformations is established. Changes of the image central moments along the distortion axis are shown
Keywords: компьютерное зрение